Interplay between Exciton and Free Carriers in Organolead Perovskite Films. Issue 1 (December 2017) - Wang, Wei; Li, Yu; Wang, Xiangyuan; Liu, Yang; Lv, Yanping; Wang, Shufeng; Wang, Kai; Shi, Yantao; Xiao, Lixin; Chen, Zhijian; Gong, Qihuang
Abstract For highly interested organolead perovskite based solar cells, the exciton and free carriers are the photoproducts in the working layers. In this study, we revealed their two forms of relations depending on heat-annealing condition. In non-annealed films and single crystal, they are in density-dependent dynamical balance (co-existing). For the sufficiently heat-annealed films, they present a significant emissive exciton-carrier collision (ECC). The two relations indicate the emergence of a subgrain morphology within the tetragonal phase of crystal grain, induced by heat annealing process. Such subgrain structure could be assigned to a ferroelastic twinning structure recently found inside the crystal grain of the films. Since the heat annealing is a general procedure in preparing perovskite working layers, we propose that the ECC and subgrain morphology widely exist in real devices. We suggest that the subgrain structure provides another level of morphological basis for in depth understanding high performance of organolead perovskite working layers.